Extreme degeneracy of inputs in firing a neuron leads to loss of information when neuronal firing is examined - Vadakkan, Kunjumon I (PeerJ Preprints, 2018)
Possible combinations of inputs in the order of 10100 can fire (axonal spike or action potential) a neuron that has nearly 104 inputs (dendritic spines). This extreme degeneracy of inputs that can fire a neuron is associated with significant loss of information when examination is limited to neuronal firing. Excitatory postsynaptic potentials (EPSPs) propagating from remote locations on the dendritic tree attenuate as they arrive at the axon hillock depending on the distance they propagate. Moreover, some EPSPs from remote locations will not even reach the axonal hillock. In this context, an operational mechanism at the location of origin of these EPSPs is necessary to preserve information for efficient storage. Evidence can be visible as the tip of an iceberg of operational mechanisms occurring only at a narrow window when sub-threshold activated (before learning) non-firing neurons fire during memory retrieval in response to a cue stimulus. Even this observation from a set of neurons does not identify the location where information is stored due to extreme degeneracy of inputs that can contribute potentials to cross the threshold and fire those neurons. In summary, it is necessary to identify locations of specific inputs where information is expected to make changes.
Keywords: Degeneracy; Action potential; Axonal spike; Neuronal firing; Information storage; Internal sensation; First-person properties; Dendritic spine; Dendritic spike; Mind